And thereby hangs a tail: morphology, developmental patterns and biomechanics of the adhesive tails of crested geckos (Correlophus ciliatus). Issue 1953 (30th June 2021) - Griffing, Aaron H.; Sanger, Thomas J.; Epperlein, Lilian; Bauer, Aaron M.; Cobos, Anthony; Higham, Timothy E.; Naylor, Emily; Gamble, Tony
Abstract : Among the most specialized integumentary outgrowths in amniotes are the adhesive, scale-like scansors and lamellae on the digits of anoles and geckos. Less well-known are adhesive tail pads exhibited by 21 gecko genera. While described over 120 years ago, no studies have quantified their possible adhesive function or described their embryonic development. Here, we characterize adult and embryonic morphology and adhesive performance of crested gecko ( Correlophus ciliatus ) tail pads. Additionally, we use embryonic data to test whether tail pads are serial homologues to toe pads. External morphology and histology of C . ciliatus tail pads are largely similar to tail pads of closely related geckos. Functionally, C . ciliatus tail pads exhibit impressive adhesive ability, hypothetically capable of holding up to five times their own mass. Tail pads develop at approximately the same time during embryogenesis as toe pads. Further, tail pads exhibit similar developmental patterns to toe pads, which are markedly different from non-adhesive gecko toes and tails. Our data provide support for the serial homology of adhesive tail pads with toe pads.